Revision of the genus Hemitrachys Gorham, with discovery of a second species (Coleoptera: Cleridae: Clerinae) - Yang, Gan-Yan; Yang, Xing-Ke (Zootaxa, 2013)
The genus Hemitrachys Gorham, 1876 is revised and a new species Hemitrachys tubericollis n. sp. from China is described as the second species of this genus. Thirty-eight illustrations of habitus, genital and external characters are provided.